Isoflavones and Bone Health - Perez-Castrillon, Jose L.; de Luis, Daniel; Hernandez, Gonzalo; Duenas-Laita, Antonio (Current Women's Health Reviews, 2009)
Osteoporosis is a highly-prevalent chronic disease that affects postmenopausal women who are clinically asymptomatic until complications, such as fractures, appear. Although the incidence of osteoporotic fractures is increasing in many parts of Asia, rates are still lower than those reported in Western countries. It has been postulated that soy intake, a major source of isoflavones, may have potentially-beneficial effects on bone health. In vitro and animal studies have shown that isoflavones exert their bone- supporting effects in multiple ways. Experimental data show that they act on both osteoblasts and osteoclasts through genomic and nongenomic pathways. Retrospective and prospective studies (case-control and cohort studies) have showed a conflicting effect of isoflavones on bone health. A small number of randomized controlled trials on the effects of soy isoflavones on bone mineral density and bone remodeling markers have been carried out. Only the Shanghai Women's Health Study has evaluated the association between soy consumption and the risk of fracture. The aim of this review was to evaluate the possible role of isoflavones in the prevention of osteoporotic fractures in postmenopausal women as demonstrated in high quality studies.
Keywords: soy